ANALISIS PENDAPATAN PETANI PADI VARIETAS CILIWUNG IRIGASI TEKNIS POLA KEMITRAAN DAN POLA MURNI DI DESA TANJUNG SARI (JASEP, 2017)
Food Security Loan (KKP) there are two patterns, namely KKP partnership pattern and pure pattern KKP. MMAF partnership schemes help farmers in the form of non-cash packages consisting of balanced fertilizer packages, blue labeled rice seeds, and pesticides to farmer groups. While the pattern of pure KKP is KKP whose funding comes from commercial banks. In the KKP program, the pattern of pure farmers get packages of seeds, fertilizers, pesticides, tillage and maintenance costs, harvest and post harvest costs. Food Security Loan (KKP) provided by the government is expected to be utilized by farmers optimally for farming activities. The problem faced is the difference of timeliness and quantity in the procurement of production factors for farmers receiving Credit Cardfill (KKP) partnership pattern and pure pattern KKP, What is the level of difference of paddy farmer income using KKP partnership pattern and pure pattern KKP. While the purpose of this research is to know the timeliness and quantity in the procurement of production factors channeled through the pattern of partnership and pure pattern, and to know the income of irrigated paddy farmers who utilize Credit of Food Security (KKP) pattern of partnership and pure pattern. And the conclusion is the average income of farmers of Ciliwung rice field varieties technical irrigation partnership pattern of Rp 3,763,800 / lg / mt. As well as the income of rice farmers Ciliwung variety of technical irrigation of pure pattern of Rp 3,775,033 / lg / mt.